Structural evolution of microfibers in seawater and freshwater under simulated sunlight: A small- and wide-angle X-ray scattering study - Astra Piccinini; Giulia Lucia; Daniele Colarossi; Paolo Principi; Heinz Amenitsch; Lucia Pittura; Francesco Regoli; Stefania Gorbi; Francesco Spinozzi (PLoS ONE, 2025)
Microfibers are pollutants of increasing concern, as they accumulate in aquatic environments and pose risks to living organisms. Once released, they undergo degradation processes that reduce their size and enhance their ability to interact with biological systems. Among these processes, photodegradation is a key driver, leading to fiber fragmentation and structural shrinkage. This study investigates the nanostructural evolution of five common microfibers (cotton, cellulose acetate, polyamide, polyester, and linen) dispersed in seawater and freshwater, following simulated solar ultraviolet exposure equivalent to one year of environmental conditions. Using synchrotron-based Small- and Wide-Angle X-ray Scattering, we characterized changes in the internal organization of the fibers. Small-Angle X-ray Scattering data were analyzed using a multiscale model that describes macrofibrils as bundles of polydisperse core-shell microfibrils arranged in a distorted hexagonal lattice. Results reveal distinct nanostructural modifications. In seawater, cotton and polyamide show increases in microfibril spacing, resulting in macrofibril enlargement, while in freshwater their structure remains more stable or evolves irregularly. Polyester and linen exhibit a progressive reduction in macrofibril diameter in both media, suggesting a greater tendency toward fragmentation. Cellulose acetate remains structurally stable in seawater but undergoes shrinkage and partial reorganization in freshwater. Wide-Angle X-ray Scattering confirms the presence of crystalline phases in cotton, linen, and polyamide, and reveals medium-specific variations in crystallite size, particularly under seawater conditions. These structural differences were quantified using Rietveld refinement of the diffraction data. The structural evolution of microfibers under environmentally relevant conditions has direct implications for their fragmentation potential, persistence, and the release or transport of adsorbed contaminants. The results underscore the importance of considering material-specific behaviors in assessing environmental persistence and potential ecological impact.